Cognitive Style and Conceptual Modeling in the Poetry of Mukagali Makatayev - Amirbekova, Aigul (Forum for Linguistic Studies, 2025)
The study of a poet’s cognitive style offers valuable insights into the interaction between individual creativity, linguistic expression, and cultural perception. This article examines the cognitive style of Mukagali Makatayev, a prominent figure in modern Kazakh literature, whose poetry intricately combines personal experience, national identity, and metaphysical reflections. The relevance of this research lies in the growing interest in cognitive approaches to literary studies, which illuminate how poets structure thought, organize imagery, and convey complex emotions through language. The aim of the study is to identify and analyze the key cognitive models in Makatayev’s poetry, including imitation, abstraction–concretization, iconic signs, and material symbolism. These models demonstrate how the poet perceives and interprets reality, shaping both the form and semantic depth of his poetic imagery. The novelty of the article consists in integrating cognitive linguistic analysis with literary interpretation, providing a systematic framework for understanding conceptual structuring and cognitive mechanisms in Kazakh poetry. The research employs qualitative content analysis, cognitive modeling, and figurative-language interpretation. Practically, the findings can enhance literary criticism, pedagogy, translation studies, and cultural preservation by offering tools to analyze poetic imagery and cognitive patterns. By revealing the underlying mechanisms of Makatayev’s creative thinking, the study contributes to both the theoretical understanding of cognitive stylistics and the practical appreciation of national literary heritage.